Energy assessment and external circulation design for LNG cold energy air separation process under four different pressure matching schemes. (October 2021) - Han, Fenghui; Wang, Zhe; Jiang, Yuemao; Ji, Yulong; Li, Wenhua
Abstract: As an emerging energy conservation approach, the combination system of LNG regasification and air separation can not only recover the low-grade cold energy of LNG, but also reduce the power consumption of traditional air separation process. This paper proposes four external circulation design schemes for the energy conversion of LNG regasification and nitrogen cooling under different pressure matching conditions to realize the cascade energy utilization of LNG cold energy air separation process. The energy and exergy thermodynamic models are built for the four schemes based on the energy balance and pinch point analysis. The Linde cycle with LNG pre-cooling is used for the model testing, and the related performance indicators of the newly designed systems are compared with the traditional and existing systems. The results indicate that the four schemes proposed in this paper can greatly reduce the energy consumption per unit liquid product, the minimum consumption of which is only 0.189 kW·h·kg −1 . In addition, with the increase of LNG pressure, the exergy loss of each scheme decreases. According to the comparison of different schemes, the external circulation with high-pressure LNG and low-pressure circulating nitrogen has the smallest LNG demand, minimum exergy loss and the largest exergy efficiency of 0.869, and the LNG volume required per unit liquid nitrogen production is 1.739 Nm 3, achieving the best LNG cold energy utilization rate.